CONGRESS OF AMERICAN HEART ASSOCIATION 2005: NEW RESULTS, NEW PROBLEMS - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
Congress of American Heart Association 2005: new results, new problems.